A sobrecarga aguda cardíaca advinda de fístula aorto-caval retarda o esvaziamento gástrico de líquidos em ratos acordados - Silva, Moisés Tolentino Bento da (2008)
In view that the behaviour of gastrointestinal tract seems to have intimate relationship with the activity of the cardiovascular system, we decided to verify whether the redistribution of blood volume through fistula aorto-caval with sizes of needles (21, 23 or 26G) affect the motility of the gastrointestinal tract in rats awaked. Male albino rats (230 to 280g) were divided into groups false-operated (FO) or designated with fistula (F), moreover, had groups fistula + bleeding (FS), fistula + vagotomy (FV) and fistula + esplancnotomy (FE), all with studied 24 hours after preparation of the fistula with needle (21G). Hemodynamic parameters of mean arterial pressure (MAP), heart rate (HR), central venous pressure (CVP) were monitored continuously and cardiac output (CO) determined by term-dilution. After the surgical procedures the rats FO and (F) had the hemodynamic parameters and gastric emptying (GE) studied in the time post-prandial (10, 20 or 30min.). The MAP of rats (F) had lower values (p <0.05) when compared to FO (116.3 ± 3.5 vs. 101.3 ± 3.3 mmHg). Moreover, in rats (F) increased (p <0.05) the values of CVP when compared to rats FO (1.9 ± 0.4 vs 5.8 ± 0.6 cmH2O), HR (365.0 ± 7.0 vs 417.0 ± 7.0 bpm) and the CO (119.9 ± 9.6 vs 172 ± 5.3 ml / min). In relation the rats the FO was a gastric retention increased in (F) in the time post-prandial 10, 20 and 30min (45.6 ± 3.6 vs 57.5 ± 2.1%; 36.4 ± 2.7 vs 50.5 ± 3.3% and 33.3 ± 2.7 vs 44.7 ± 3.0%, respectively). The rats of the group (FS), showed values of (GE) lower than the animals (F) (36.5 ± 3.2 vs 50.5 ± 3.3%, p <0.05) but similar to FO ( 36.4 ± 2.7%). The vagotomy (FV), it reversed the delay in the (GE) induced by fistula (F) (40.4 ± 2.3 vs 50.5 ± 3.3%), in contrast, the rats undergoing esplancnotomy (FE) showed no differences in comparation with the (F) (50.5 ± 3.3 and 50.1 ± 1.4%). Moreover, was not found involvement of acid secretion in the delays of the (GE) after fistula. Therefore, the overload heart arisen from arteriovenous fistula with needles, size (21, 23 or 26G) to promote changes in hemodynamic parameters, leads decreases the (GE) and interfere in the intestinal transit of liquids in rats awaked. This delay in the (GE) was also abolished after bleeding or prior the subdiaphragmatic vagotomy, but no change after esplancnotomy.